1995
DOI: 10.1038/373151a0
|View full text |Cite
|
Sign up to set email alerts
|

Reduced hippocampal LTP and spatial learning in mice lacking NMDA receptor ε1 subunit

Abstract: The NMDA (N-methyl-D-aspartate) receptor channel is important for synaptic plasticity, which is thought to underlie learning, memory and development. The NMDA receptor channel is formed by at least two members of the glutamate receptor (GluR) channel subunit families, the GluR epsilon (NR2) and GluR zeta (NR1) subunit families. The four epsilon subunits are distinct in distribution, properties and regulation. On the basis of the Mg2+ sensitivity and expression patterns, we have proposed that the epsilon 1 (NR2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

39
531
4
6

Year Published

1995
1995
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 797 publications
(580 citation statements)
references
References 30 publications
39
531
4
6
Order By: Relevance
“…Mice lacking the el subunit have reduced hippocampal LTP and spatial learning [22], The E1/(I receptor is postnatally expressed and widely distributed in the brain and e4/(l receptors are present in the diencephalon and brainstem from the embryonic, through the neonatal stage [7]. Both the receptors were inhibited by Pb 2+ at the low concentration shown in the present experiment.…”
Section: Efjects Of Pb :+supporting
confidence: 53%
“…Mice lacking the el subunit have reduced hippocampal LTP and spatial learning [22], The E1/(I receptor is postnatally expressed and widely distributed in the brain and e4/(l receptors are present in the diencephalon and brainstem from the embryonic, through the neonatal stage [7]. Both the receptors were inhibited by Pb 2+ at the low concentration shown in the present experiment.…”
Section: Efjects Of Pb :+supporting
confidence: 53%
“…Activation of NMDARs is essential for long-term potentiation and spatial learning and memory (Malenka and Bear, 2004), and NMDAR blockade results in impaired synaptic plasticity manifested as adverse effects on learning and memory (Sakimura et al, 1995;Shimizu et al, 2000). It has been shown that higher doses of ketamine can induce neuroapoptosis in rodents (Maxwell et al, 2006;Olney et al, 2002a;Wang et al, 2005) and primates (Haberny et al, 2002;Slikker et al, 2007b;Wang et al, 2006) during early development.…”
Section: Discussionmentioning
confidence: 99%
“…For example, dysfunction or blockade of the NMDA receptor leads to a deficiency in learning in mice/ rats. 30,31 Moreover, a toluene-induced reduction of hippocampal glutamate in mice is accompanied by a poor learning performance. 32 Also in human beings, several studies suggest a link between decreased glutamatergic neurotransmission and hippocampal functions.…”
Section: Discussionmentioning
confidence: 99%